Borrowing legitimacy as English learner (EL) leaders: Indiana's 14-year history with English language proficiency standards. (April 2017) - Morita-Mullaney, Trish
English language proficiency or English language development (ELP/D) standards guide how content-specific instruction and assessment is practiced by teachers and how English learners (ELs) at varying levels of English proficiency can perform grade-level-specific academic standards in K–12 US schools. With the transition from the state-developed Indiana ELP/D standards adopted in 2003 to the World Class Instructional Design and Assessment (WIDA) English language development standards adopted in 2013, this paper explores Indiana's ELP/D standard's 14-year history and how its district EL/Bilingual district leaders have interpreted and implemented these two sets of standards between the school years 2002–03 and 2015–16. Using critical leadership and feminism within a narrative design, EL/Bilingual leaders illuminate distinct leadership logics as they mediate and implement ELP/D standards in their districts. Academic content standards are regarded with greater privilege, complicating how EL/Bilingual leaders can position ELP/D standards. Restricted by this standards hierarchy, EL/Bilingual leaders found limited educational venues in which to discuss the performance-based nature of ELP/D standards. Implications for assessment, policy, and leadership preparation are discussed.